Legal Perspectives on the Slaying of Laban - Welch, John W. (Journal of Book of Mormon studies, 1992)
This article marshals ancient legal evidence to show that Nephi's slaying of Laban should be understood as a protected manslaughter rather than a criminal homicide. The biblical law of murder demanded a higher level of premeditation and hostility than Nephi exhibited or modern law requires. It is argued that Exodus 21:13 protected more than accidental slayings or unconscious acts, particularly where God was seen as having delivered the victim into the slayer's hand. Various rationales for Nephi's killing of Laban are explored, including ancient views on surrendering one person for the benefit of a whole community. Other factors within the Book of Mormon as well as in Moses' killing of the Egyptian in Exodus 2 corroborate the conclusion that Nephi did not commit the equivalent of a first-degree murder under the laws of his day.